Development of Toxic Effect Risk Model For Inherent Safety Design - Shariff, Khadeeja (Universiti Teknologi Petronas, 2005)
Safety and environmental risk assessments are done in parallel or when the design stage of the process plant is almost completed. Analysis of safety conducted at the last stage exposes the plant to various hazards. The objective of this project is to develop a model to predict the concentration levels and toxic effect of accidental gaseous release as an inherent safety approach to process plant design. For this simulation, the author develops a two-dimensional Gaussian plume model into Microsoft Excel Worksheet applications. The Gaussian model developed predicts concentrations from one point source at ground level to determine the effect of toxic releases to receptors close to the ground (people, plants and animals). Input data requirements for this model include the physical properties of the gaseous component such as its density, temperature, specific heat and its volumetric flowrate. The model takes into account atmospheric and meteorological conditions, requiring data input such as the ambient temperature, wind velocity, wind stability category and the area class. The author simulated the model hypothetically on two industrial toxic releases, Ammonia (NH3), a gas lighter than air and Sulfur Dioxide (SO2), a dense gas. The distance of rupture from ground level, the diameter of the rupture and the time of exposure are set similar for both simulations to compare the effects of dense gas toxic releases with that of light gases. Results showed that both gases have an almost similar peak concentration of 70.34 ppm for NH3 and 69.98 ppm for S02. As the toxic cloud moves further downwind, the concentration of NH3 disperses faster than that of SO2. The difference in this is the factor of buoyancy flux. NH3 produces a positive buoyancy flux. Since SO2 is a dense gas, the plume tends to slump and spread out in thick clouds rather than float buoyantly into the air. For SO2, plume rise is small, producing a negative plume rise. Approaching 100km downwind, the difference in concentrations of SO2 and NH3 increases twice as much. Although the peak concentrations are almost similar, the extent of risk exposure differs greatly. Probit values for NH3 ranges from - 50.26 to -17.19 while the Probit range for S02 is from -20.71 to -3.37.This measurement of the probability of death shows 60-80% higher Probit values of S02 as compared to NH3. Results prove that denser gas has a higher adverse effect than lighter gas. For this simulation, both gases do not reach the IDLH limits (Immediately Dangerous to Life and Health) but the produced concentrations can cause dizziness, disorientation and restricted visual. The author also modeled the toxic release of NH3 on different wind stability conditions, permitting to PasquuTs wind stability category. Results show that unstable wind conditions (wind stability category A) give lower levels of concentration (peak concentration 13 ppm) as compared to the toxic release under stable wind conditions (wind stability category F) where peak concentrations mounted to 1,023 ppm.